Adiponectin Ameliorates Intrauterine Adhesion-Related Endometrial Inflammation and Fibrotic Changes by Downregulating the NLRP3/IL-1β/TGF-β1 Axis - Yang, Wenmei; Li, Qiaoxia; Zhang, Yongyan; Zhi, Zhifu (Current Molecular Medicine, 2025)
<span class=
Keywords: TGF-β1